Modeling Ca2+ signals: understanding Ca2+ regulatory networks in cells: introduction and basic concepts - Friel, David (Henry Stewart Talks, 2021)
Calcium signals, Modeling calcium signals, Development of dynamic calcium signaling models, The fundamental equation, Calcium buffers, Deriving the fundamental calcium dynamics equation, Calcium fluxes